Work productivity in rhinitis using cell phones: The MASK pilot study. Issue 10 (9th June 2017) - Bousquet, J.; Bewick, M.; Arnavielhe, S.; Mathieu‐Dupas, E.; Murray, R.; Bedbrook, A.; Caimmi, D. P.; Vandenplas, O.; Hellings, P. W.; Bachert, C.; Anto, J. M.; Bergmann, K. C.; et al.
Abstract: Allergic rhinitis often impairs social life and performance. The aim of this cross‐sectional study was to use cell phone data to assess the impact on work productivity of uncontrolled rhinitis assessed by visual analogue scale (VAS). A mobile phone app ( Allergy Diary, Google Play Store and Apple App Store) collects data from daily visual analogue scales (VAS) for overall allergic symptoms (VAS‐global measured), nasal (VAS‐nasal), ocular (VAS‐ocular) and asthma symptoms (VAS‐asthma) as well as work (VAS‐work). A combined nasal‐ocular score is calculated. The Allergy Diary is available in 21 countries. The app includes the Work Productivity and Activity Impairment Allergic Specific Questionnaire (WPAI:AS) in six EU countries. All consecutive users who completed the VAS‐work from 1 June to 31 October 2016 were included in the study. A total of 1136 users filled in 5818 days of VAS‐work. Symptoms of allergic rhinitis were controlled (VAS‐global <20) in approximately 60% of the days. In users with uncontrolled rhinitis, approximately 90% had some work impairment and over 50% had severe work impairment (VAS‐work >50). There was a significant correlation between VAS‐global calculated and VAS‐work (Rho=0.83, P <0.00001, Spearman's rank test). In 144 users, there was a significant correlation between VAS‐work and WPAI:AS (Rho=0.53, P <0.0001). This pilot study provides not only proof‐of‐concept data on the work impairment collected with the app but also data on the app itself, especially the distribution of responses for the VAS. This supports the interpretation that persons with rhinitis report both the presence and the absence of symptoms.